2017
DOI: 10.22161/ijeab/2.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pruning on Diameter and Height Growth of Pinus nigra Arnold subsp. pallasina Plantations in Turkey

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pruning the lower third of the tree crown (T2) was higher in diameter growth, indicating that this pruning intensity has no negative effect on radial increment, but rather benefits its increase. This agrees with that found by Tonguc and Guner (2017) in Pinus nigra J. F. Arnold, who reported that the effect of pruning 25 % of the crown showed a tendency of a higher increment than the rest of the treatments.…”
Section: Resultados Y Discusiónsupporting
confidence: 93%
See 3 more Smart Citations
“…Pruning the lower third of the tree crown (T2) was higher in diameter growth, indicating that this pruning intensity has no negative effect on radial increment, but rather benefits its increase. This agrees with that found by Tonguc and Guner (2017) in Pinus nigra J. F. Arnold, who reported that the effect of pruning 25 % of the crown showed a tendency of a higher increment than the rest of the treatments.…”
Section: Resultados Y Discusiónsupporting
confidence: 93%
“…Although there is a negative relationship between pruning intensity and diameter increment, except for the light pruning treatment (T2), it can be assumed that the removal of ineffective branches may benefit tree growth (Nyland et al, 2016;Tonguc & Guner, 2017). The results coincide with the studies of Cown (1972) and Ferrere et al (2015) in Pinus radiata D. Don, who report that pruning the lower third of the tree crown benefits radial growth.…”
Section: Dhb Increase (Cm) / Incremento En Dn (Cm)supporting
confidence: 69%
See 2 more Smart Citations
“…It should also be considered that the evaluated periods could have been insufficient for P. greggii to show the positive effects of pruning on its growth since in a study on Pinus nigra Arnold subsp. pallasina, pruning improved growth in height and diameter up to 12 years after its application (Tonguc & Guner, 2017).…”
Section: La Soledad Canatlán Durango Statementioning
confidence: 98%